Association between Sclerosing Cholangitis and Paget Disease: Diagnostic Difficulties - Sabbah Meriam; Bibani Norsaf; Trad Dorra; Ouakaa Asma; Elloumi Héla; Gargouri Dalila (Journal of Spleen And Liver Research, 2018)
A rare case of association between primary sclerosing cholangitis and Paget's disease emphasizing the diagnostic difficulties in front of increased alkaline phosphatase is reported. The association between sclerosing cholangitis and Paget's disease wasn’t yet described and could thus be coincidental. However, our observation underlines the benefit of dosing ALP isoenzyme to characterize the bone or hepatic origin of ALP and therefore, help to guide the diagnosis.
Keywords: Cholangitis